Histone deacetylase inhibition has cardiac and vascular protective effects in rats with pressure overload cardiac hypertrophy - Jung, H; Lee, E; Kim, I; Song, J. H; Kim, G. J (Physiological research, 2019)
Histone deacetylase (HDAC) inhibitors have shown beneficial effects in animal models of cardiovascular diseases. We hypothesized that HDAC inhibitor, sodium valproate (VPA), has cardiac and vascular protective effects in rats with pressure overload cardiac hypertrophy induced by transverse aortic constriction (TAC). Sections of the heart were visualized after hematoxylin and eosin staining, picrosirius red staining and immunohistochemistry. The expression of genes related to cardiac hypertrophy, fibrosis, and oxidative stress was determined by quantitative real-time polymerase chain reaction. The aortic ring tension analysis was conducted using both the ascending aorta and descending thoracic aorta. TAC increased the expression of hypertrophic, fibrotic, and oxidative stress genes, which was attenuated by VPA. In the ascending aorta with intact endothelium, there was a significant decrease in the relaxation response, which was recovered by VPA treatment. These results indicate that VPA has cardiac and vascular protective effects in rats with pressure overload cardiac hypertrophy.
Keywords: arteriální tlak; kyselina valproová; potkani Sprague-Dawley; modely nemocí na zvířatech; Rats, Sprague-Dawley; myokard; ligace; Valproic Acid; zvířata; Histone Deacetylase Inhibitors; Vasodilation; aorta; Fibrosis; Ligation; Disease Models, Animal; funkce levé komory srdeční; regulace genové exprese; oxidační stres; Gene Expression Regulation; vazodilatancia; mužské pohlaví; Arterial Pressure; Hypertrophy, Left Ventricular; inhibitory histondeacetylas; Oxidative Stress; Ventricular Remodeling; hypertrofie levé komory srdeční; vazodilatace; fibróza; remodelace komor; Animals; Vasodilator Agents; Myocardium; Ventricular Function, Left; Male; Aorta